Vedolizumab-Induced Liver Injury - Saraiva,Miguel Mascarenhas (2021)
Abstract: Drug-induced liver injury is an important cause of acute liver injury. Immunomodulatory therapies, such as vedolizumab (VDZ), are being increasingly used for the treatment of several diseases, most importantly inflammatory bowel disease. Several studies have demonstrated the safety of this substance. To date, only one post-marketing study has reported a case of hepatotoxicity attributable to VDZ. The authors present the case of a 41-year-old woman followed at the gastroenterology outpatient clinic for ulcerative colitis (UC) and autoimmune hepatitis (AIH). This patient was being treated with low-dose glucocorticoids for AIH (prednisolone 10 mg), with adequate disease control. Additionally, she was being treated with oral salicylates (mesalamine 3 g/day) and oral budesonide (9 mg/day) for her UC. For uncontrolled UC, she was started on VDZ. Two weeks after the first infusion of VDZ, the patient developed a clinical and analytical phenotype compatible with acute hepatitis. Diagnostic workup for causes of hepatocellular liver injury retrieved no results. A liver biopsy corroborated the diagnosis of toxic hepatitis overlapping chronic liver disease. VDZ was withdrawn and the patient experienced complete recovery of liver tests over the following weeks. In this case report, we present the first post-marketing case of hepatocellular liver injury in probable relation to VDZ.